Peningkatan Hasil Belajar Siswa Dalam Pembelajaran IPA Berbasis Mind Map di kelas III SD Negeri 07 Situjuh Gadang, Kabupaten Lima Puluh Kota - Ira Dewi Hariani (JPGI (Jurnal Penelitian Guru Indonesia), 2020)
This research is motivated by the desire to improve the learning process that has been done with the aim of improving student learning outcomes by applying a Mind Map-based learning model to science subjects. This research is a classroom action research (PTK) using a qualitative approach conducted on students of class III at SD Negeri 07 Situjuh Gadang, Lima Puluh Kota. The problem being solved stems from the problem of practical learning in class in a professional manner. The procedure of conducting this research consists of two cycles that follow the basic principles of general classroom action research. The instrument of this research is the TK / SD supervisor as the observer and the writer himself as the planner and executor of learning in the classroom. The data obtained in this study were analyzed using qualitative data analysis which was analyzed starting from data collection to all data collected. From the results of data processing it was found that the application of Mind Map-based learning to third grade students at SD Negeri 07 Situjuah Gadang on natural science subjects could improve student learning outcomes.